Structure Design and Simulation Analysis of the Dynamic Inspection Instrument for Middle and Large Worm Gear Pairs - Duan Yuancong; Zheng Yong; Peng Donglin; Xu Shi; Wang Yangyang (Jixie chuandong)
In order to improve the detection level of transmission error of worm gear pairs, an instrument suitable for measuring transmission error of middle and large worm gear pairs is designed. This research describes the basic framework of the transmission error detection system and the overall design of the instrument. The working principle of the instrument is introduced, and the idea of integrating the time-grating sensor and the related parts of the instrument is put forward. SolidWorks is used to design the key parts and complete the structure layout and virtual assembly. Finite element analysis and structural optimization are carried out on the beam assembly by the Ansys Workbench. After optimization, the first-order natural frequency increases by 23.95%, and the corresponding amplitudes of all natural frequencies decrease significantly.